Trust in science and COVID-19 vaccination: The role of institutional trust - Janić Ognjen; Lazić Milica; Ljevaja Milica (Psihološka Istraživanja, 2024)
This study aims to investigate the moderating role of institutional trust (i.e., trust in the authorities and trust in the healthcare system) in the relationship between trust in science/official modern medicine and the attitudes of young people towards getting the COVID-19 vaccine. The sample consisted of 791 participants from Serbia (59.9% female), with an age range between 15 and 25 (M = 18.25, SD = 2.670). All trust-related measures, including trust in science, official modern medicine, the authorities and healthcare system had significant main effects in all tested models, indicating that, with an increase in the trust-related measures, the attitudes towards getting the COVID-19 vaccine tended to get more positive. Two out of four tested interactive effects were statistically significant: the interactive effect of trust in science and trust in healthcare, and trust in the official modern medicine and trust in healthcare on the attitudes towards getting COVID-19 vaccine. The study results suggest that distrust in the healthcare system is a vulnerability factor in the afore-mentioned relationship. This prompts a critical examination of the factors and conditions contributing to the pervasive lack of trust among young people in Serbia towards the institutional entities that shape and perpetuate perceptions and attitudes towards vaccination.